2023
DOI: 10.2224/sbp.12145
|View full text |Cite
|
Sign up to set email alerts
|

Influence of instructor humor on learning engagement in the online learning environment

Abstract: Using instructional humor processing theory, in an online learning setting we explored the relationships between instructor humor types as perceived by students and the students' learning engagement. This study recruited 1,829 participants. The results revealed the following: (a) Course-related, courseunrelated, self-disparaging, and aggressive instructor humor were associated with behavioral, emotional, and cognitive engagement; (b) positive emotions mediated the relationships between course-related, course-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Firstly, the results revealed that FLE positively affected online learning engagement. This finding is consistent with previous research that suggests that positive affective factors like enjoyment influence online learning engagement (Artino, 2012 ; Deng et al, 2022 ; Guo, 2021 ; Luo et al, 2023 ). FLE has been shown to promote language learning motivation and engagement (Dewaele & MacIntyre, 2014 ), and our study extends this finding to the online learning context.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Firstly, the results revealed that FLE positively affected online learning engagement. This finding is consistent with previous research that suggests that positive affective factors like enjoyment influence online learning engagement (Artino, 2012 ; Deng et al, 2022 ; Guo, 2021 ; Luo et al, 2023 ). FLE has been shown to promote language learning motivation and engagement (Dewaele & MacIntyre, 2014 ), and our study extends this finding to the online learning context.…”
Section: Discussionsupporting
confidence: 93%
“…FLE affects online learning engagement. In light of some studies which have found that motivation and enjoyment are key factors in predicting engagement in online learning activities (Deng et al, 2022 ; Guo, 2021 ; Luo et al, 2023 ), it is warranted to assume that individuals who enjoy learning a foreign language will be more engaged in online learning activities related to that language.…”
Section: Literature Reviewmentioning
confidence: 99%